HUBUNGAN KOMPENSASI DENGAN KINERJA KARYAWAN FOOD AND BEVERAGE DEPARTMENT DI HOTEL GRAND CENTRAL PEKANBARU - Saputri, Darnita Leoni; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Human Resource Management is very important in a company, one of which is engaged in the hotel industry. The Company provides fair and reasonable compensation to employees is expected to motivate employees to improve their performance. The purpose of this research are: (1) to know the compensation policy given to the employees by the management of Grand Central hotel Pekanbaru; (2) to find out the general description of employees performance of food and beverage at grand central hotel; (3) to know the compensation relationship to employees' performance of food and beverage department at grand central hotel Pekanbaru. Data processing is done by Product moment Correlation test from Pearson. From the results of the study concluded that there is a positive and significant relationship between compensation with employee performance in the company. Shown with the results of correlation coefficient test (R) of 0.836 with a significance of 0.000.Keywords: compensation, employee performance